Control active power filter for improving power quality in the micro-grid - Mohd. Zin, Abdullah Asuhaimi (2013)
This paper aims at improving the power quality with controlling method shunt active power filter in Microgrid System. A hybrid compensation system consisting of an active filter and passive filters in the Micro-grid is discussed. Passive filter is connected to a distortion source and designed to eliminate main harmonics and supply reactive power for the distortion source, while the active filter is applied to the correction of the unbalance condition a system and cancellation of the remaining harmonics. In order to examine the proposed method, simulations are carried out in the case of the distribution system with dynamic nonlinear loads and Micro turbine. Several dynamic nonlinear loads without any filters using just shunt active filter, passive filter and the proposed hybrid structure. The performance of the proposed system was analyzed and simulated via MATLAB software. The results confirm the validity of the proposed approach to eliminate undesired harmonic and distortion.